UPLCeMS/MS for simultaneous determination of aflatoxins, ochratoxin A, zearalenone, DON, fumonisins, T-2 toxin and HT-2 toxin, in cereals - Soleimany, F.; Jinap, Selamat; Abas, Faridah; Khatib, Alfi (Elsevier, 2012)
An ultra-performance liquid chromatography tandem mass spectrometry (UPLCeMS/MS) method is described for simultaneous determination of aflatoxins (AFB1, AFB2, AFG1 and AFG2), ochratoxin A (OTA), zearalenone (ZEA), deoxynivalenol (DON), fumonisins (FB1 and FB2), T-2 and HT-2 toxins in cereals. Mycotoxins were separated by reverse phase liquid chromatography (RP-LC) and detected by tandem mass spectrometry using an electro spray-ionization interface (ESI) in both positive- and negative- ion modes. The mean recoveries of mycotoxins from spiked cereals ranged from 83.5% to 107.3%, whereas the limit of detection (LOD) and limit of quantification (LOQ) ranged from 0.01 to 25 ng/g and 0.02e40 ng/g, respectively. The multi-mycotoxin method developed in this work was applied for the simultaneous determination of mycotoxins in 80 cereal samples collected from Malaysian markets. A total of 60 cereal samples (75%) were contaminated with at least one of these mycotoxins at levels greater than the LOD. Only one maize sample and two rice samples were contaminated at levels exceeding the European regulatory limits for aflatoxins and OTA (4 and 5 ng/g, respectively). The rates of the occurrence of mycotoxins in the commercial cereal samples were 50, 30, 19, 30, 16, 14, 14 and 12% for the aflatoxins (the total amount of AFB1, AFB2, AFG1 and AFG2), OTA, ZEA, DON, FB1, FB2, T-2 and HT-2 toxins, respectively. The results demonstrated that the procedure was suitable for the simultaneous determination of these mycotoxins in cereals and could be performed for their routine analysis in mycotoxin laboratories.